2021
DOI: 10.1126/sciadv.abh0050
|View full text |Cite
|
Sign up to set email alerts
|

Brain inflammation triggers macrophage invasion across the blood-brain barrier in Drosophila during pupal stages

Abstract: The nervous system is shielded from circulating immune cells by the blood-brain barrier (BBB). During infections and autoimmune diseases, macrophages can enter the brain where they participate in pathogen elimination but can also cause tissue damage. Here, we establish a Drosophila model to study macrophage invasion into the inflamed brain. We show that the immune deficiency (Imd) pathway, but not the Toll pathway, is responsible for attraction and invasion of hemolymph-borne macrophages across the BBB during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 91 publications
0
25
0
Order By: Relevance
“…ApoE also promotes neutrophil activation [ 241 ] and mediates antigen presentation on natural-killer cells [ 242 ]. Macrophages will also infiltrate through the BBB during neuroinflammation [ 243 , 244 ], and it has been demonstrated that LPS can repress APOE gene expression in macrophages through the Tpl-2/MEK/ERK pathway [ 245 ]. Interestingly, even if the implications of adaptative immunity in AD are still largely unknown, promising small-scale studies suggest the implication of specialized CD8 T cells linked to the AD neurodegenerative process [ 246 ].…”
Section: Apoe In the Neuroinflammatory Responsementioning
confidence: 99%
“…ApoE also promotes neutrophil activation [ 241 ] and mediates antigen presentation on natural-killer cells [ 242 ]. Macrophages will also infiltrate through the BBB during neuroinflammation [ 243 , 244 ], and it has been demonstrated that LPS can repress APOE gene expression in macrophages through the Tpl-2/MEK/ERK pathway [ 245 ]. Interestingly, even if the implications of adaptative immunity in AD are still largely unknown, promising small-scale studies suggest the implication of specialized CD8 T cells linked to the AD neurodegenerative process [ 246 ].…”
Section: Apoe In the Neuroinflammatory Responsementioning
confidence: 99%
“…For the mammalian blood-brain barrier passage through tricellular junctions is detected most frequently ( Dias et al, 2021 ). In invertebrates, breaching of an intact blood-brain barrier has been described only recently in response to glial immunity induction ( Winkler et al, 2021 ). However, a preferred passage route into the nervous system is not yet known.…”
Section: Tiling Of Drosophila Surface Glial Cellsmentioning
confidence: 99%
“…However, a preferred passage route into the nervous system is not yet known. Once macrophages have entered the nervous system, they move toward the neuropil, where they start to phagocytose synaptic material ( Winkler et al, 2021 ).…”
Section: Tiling Of Drosophila Surface Glial Cellsmentioning
confidence: 99%
“…A recent study has documented that Drosophila pupal macrophages cross the blood-brain barrier upon receiving a PDGF-like factor, Pvf2, signal from glial cells that is induced by infection ( 90 ). Such signals have also been described for the developmental migration of hemocytes and their invasion of the embryonic epithelium ( 91 , 92 ).…”
Section: Resultsmentioning
confidence: 99%